ULTIMOS ESTUDIOS SOBRE LA TRANSFUSION DE MODULA - SANCHEZ YLLADES (Secretaría Salubridad y Asistencia, CD MEXICO, DF, MEX, 1944)
Bone marrow transfusions were carried out in 2 cases of pulmonary tuberculosis, one case of pulmonary abscess, 2 cases of syphilitic hepatitis and 1 case of glomerulonephritis In both cases of tuberculosis, the anemia and general condition of the patient
REV MEX MED
Keywords: ESTUDIOS, TRANSFUSION, MODULA; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA